Pengaruh Sarana Prasarana, Kepemimpinan dan Kompetensi terhadap Kinerja Guru dan Implikasi pada Prestasi Peserta Didik di SMP Negeri 4 Mandau dan Pinggir Tahun Pelajaran 2022/2023 - Reni Dewita; Suarni Norawati; Abshor Marantika (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
This research aims to determine and analyze the influence of Infrastructure, Leadership and Competence on Teacher Performance and the Implications for student achievement at SMPN 4 Mandau and Pinggir. This research uses quantitative descriptive methods. The data used are primary data and secondary data resulting from distributing questionnaires, observations and recorded documents. Data collection techniques use questionnaire and documentation techniques. The analysis technique used is statistical analysis, namely multiple linear regression analysis with hypothesis verification through the t test to prove the relationship between the independent variable and the dependent variable partially. The F test is to prove the relationship between the independent variable and the dependent variable simultaneously. The population in this study were teachers at SMPN 4 Mandau and Pinggir, totaling 114 teachers and also the sample. This research also uses a purposive random sampling technique. The results of this research prove that (1) Infrastructure influences teacher performance, (2) Principal leadership simultaneously influences teacher performance (3) teacher professional competence is the variable that dominantly influences teacher performance